2018
DOI: 10.1007/s11027-018-9803-2
|View full text |Cite
|
Sign up to set email alerts
|

Subsidence and carbon dioxide emissions in a smallholder peatland mosaic in Sumatra, Indonesia

Abstract: Most attention in quantifying carbon dioxide (CO2) emissions from tropical peatlands has been on large-scale plantations (industrial timber, oil palm (Elaeis guinensis)), differing in drainage and land-use practices from those of smallholder farms. We measured subsidence and changes in bulk density and carbon organic content to calculate CO2 emissions over 2.5 years in a remnant logged-over forest and four dominant smallholder land-use types in Tanjung Jabung Barat District, Jambi Province, Sumatra, Indonesia:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 61 publications
0
45
0
2
Order By: Relevance
“…The results showed that mixed oil palm achieved the targets. On peat soils subsidence and carbon emissions are so high in smallholder systems that intercropping won't help to reduce emissions (Khasanah and van Noordwijk, 2018). The land equivalent ratio (LER P ) of oil palm + cocoa intercrop exceeds 1 (1.44), while for oil palm + pepper it is 0.99.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that mixed oil palm achieved the targets. On peat soils subsidence and carbon emissions are so high in smallholder systems that intercropping won't help to reduce emissions (Khasanah and van Noordwijk, 2018). The land equivalent ratio (LER P ) of oil palm + cocoa intercrop exceeds 1 (1.44), while for oil palm + pepper it is 0.99.…”
Section: Discussionmentioning
confidence: 99%
“…Peat conservation in its pristine state was supported with three publications refuting some earlier publications that claimed peat conversion had its merits with lesser CO 2 fluxes from oil palm plantations compared to peat swamp forest (Melling, 2005;. Studies by Wijedasa et al (2018), Dommain et al (2018 and Khasanah and Noordwijk (2019) implicated the carbon emission found in oil palm plantations planted on peat was far more damaging than its pristine state. Wijedasa et al (2018) went on further by suggesting Indonesian government to carry out legislation and policy in the country, which could in return provide a significant reduction in emission.…”
Section: Sustainable Upstreammentioning
confidence: 93%
“…Gambut dapat menyimpan/ menyerap air hingga 1.000% dari berat volume keringnya (Rochmayanto et al, 2010), dan dalam keadaan jenuh, gambut Jurnal Analisis Kebijakan Kehutanan Vol. 16 No.2, November 2019 : 133-143 Tabel (Khasanah & van Noordwijk, 2019), dan jika terjadi kebakaran pada lahan gambut; fungsi tata air dapat menghindarkan kemungkinan keluarnya biaya restorasi akibat kebakaran lahan yang diperkirakan sebesar US$1.000 per hektar (Glauber, Sarah, Adriani, & Gunawan, 2016).…”
Section: Tata Airunclassified